Innovation and public procurement: from fragmentation to synthesis on concepts, rationales and approaches. Issue 4 (2nd October 2022) - Lenderink, Bart; Halman, Johannes I.M.; Voordijk, Hans
Abstract : Public sector procurement is increasingly seen as an important instrument for inducing innovation in the private sector. Yet, a broad range of different concepts, each with their own associated rationales, and approaches, are used in literature and practice to describe the stimulation of innovation through public procurement. Due to a lack of an overview on the use of concepts, rationales and approaches to stimulate innovation through public procurement in literature and practice, it remains difficult for public organisations to decide why, how, and to what extent they will stimulate innovation in the private sector through public procurement. The contributions of this article to mitigate this problem are threefold. First, it provides a review of the different streams of literature, dichotomies and typologies on public procurement with respect to inducing innovation. Second, it discusses various approaches to stimulate innovation through public procurement individually and compares them in a structured overview. Finally, it provides guidance on the suitability of the use of these approaches in different situations.